Inverstigações experimentais da eficiência hidráulica em bocas-de-lobo em greide contínuo - Jose Geraldo de Araujo Lima (2007)
In order to guarantee that rainwater flow occurs in oriented ways and under given criteria, its necessary that installed drainage system works properly. Population´s discomfort and risks of drainage system failures become more intense when the problem is related to water capturemechanisms, responsible for exhaustiing the water that flows in the streets. In urban drainage system, dynamic inlets lead the role of capture the water that flows in gutters. In order to design and install efficient drainage systems it is increasingly important to acquire full knowledge of inlets general characteristics and efficiencies. In order to study inlets hydraulic behavior used nowadays in Belo Horizonte, a small-scalemodel that represents a street, with citys standard gutter and inlet, has been built at the UFMGs Centro de Pesquisas Hidráulicas CPH. The model has been built in 1:3-scale, using naval wood with fiberglass and resin covering. It has been installed on a steel structure with a hinge, to vary the longitudinal grade. Model has been connected to a pump able toprovide test flow values. It has been possible to observe inlets behavior details and to compute the hydraulic efficiency of those devices under given work conditions. Among the results is the computation of capture capacity of inlets located in continuous streets. Tests have shown that, for combination inlets, grate is responsible for capture almost all flow, and the curb opening doesnt have a significant contribution to inlet performance. Depression contribution to inlet capture capacity is about 12%. In addition, other grate types have been tested, in order to improve inlet capture efficiency. A grate with transversal bars located under longitudinal bars has allowed an increase of 10% in the inlet capture capacity.